What industry can do to make engineering education relevant to their own operations? - Mohd. Ghazali, Mohd. Zulkifli (1995)

(untitled)
This paper presents the scenario of engineering education in Malaysia and the national "development policy with respect to efforts towards achieving a developed nation status. "The paper discusses engineering education issues including the concepts of-engineering education in the universities and argues that 'relevance' to industry and current needs, within the bounds of the generally accepted criteria of university education, could be enhanced through good Industry University link, such link includes the role of industries in advising engineering curricula in universities. act